The use of lowcost simulation in a resourceconstrained teaching environment - M Mwandri; M Walsh; J Frantz; R Delport (South African Medical Association, 2017)
Background. To improve the management of chest trauma at the University of Botswana, Gaborone, Botswana, we incorporated simulation into a theory-basedchest trauma module by developing procedural guides, checklists and low-cost simulation.Objectives. To assess the suitability of low-cost simulation-based training and its impact on students’ proficiency, as well as its general acceptability.Methods. A total of 39 medical students who completed their surgical rotation and 20 intern doctors in their first clinical rotation participated. A checklist was used in a pre- and post-test design to assess procedural proficiency, and a rating system categorised scores. Thirteen content-based items assessed the students’ knowledge relating to the diagnosis and management of a chest injury and one item assessed their ability to perform the procedure correctly. A questionnaire was administered after the second assessment to evaluate the acceptability of the training module. Findings were summarised by median, proportion and range, and pre- and post-test outcomes were compared by Student’s paired t-test.Results. Pre- and post-test assessment scores differed significantly (median (range) 11.3 (4.5 - 21.0) and 19.5 (15.5 - 23.0), respectively (p<0.001)). The proportions of participants’ scores categorised as ‘full proficiency’ rose from 7% to 42%, and ‘reasonable proficiency’ from 30% to 60%, while both ‘some proficiency’ and ‘poor proficiency’ decreased from 50% and 20% to 0%. Most (93%) participants ‘strongly agreed’ that the training module was acceptable.Conclusion. Our results demonstrate the suitability of low-cost simulation for training and assessment in resource-constrained settings.